2021
DOI: 10.3389/fped.2021.606611
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Red Blood Cell Transfusion Using Small Central Lines in Neonates: An in vitro Non-inferiority Study

Abstract: Aim: This study aimed to investigate the safety of transfusing red blood cell concentrates (RBCCs) through small [24 gauge (24G)] and extra-small [28 gauge [28G)] peripherally inserted central catheters (PICCs), according to guidelines of transfusion practice in Switzerland.Methods: We performed a non-inferiority in vitro study to assess the safety of transfusing RBCC for 4 h at a 4 ml/h speed through 24G silicone and 28G polyurethane PICC lines, compared with a peripheral 24G short catheter. The primary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 12 publications
1
15
0
2
Order By: Relevance
“…These results were similar to those identified by researchers who simulated transfusion with a nonvalved 1F PICC 30 cm in length 19. Another study did not show statistically different hemolysis values between 1F and 2F PICCs 3. Currently, the Infusion Nurses Society does not have specific standards of practice on central VAD size for pediatric or neonatal blood transfusions.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results were similar to those identified by researchers who simulated transfusion with a nonvalved 1F PICC 30 cm in length 19. Another study did not show statistically different hemolysis values between 1F and 2F PICCs 3. Currently, the Infusion Nurses Society does not have specific standards of practice on central VAD size for pediatric or neonatal blood transfusions.…”
Section: Discussionsupporting
confidence: 82%
“…Considering the quality standards of blood banks, those values would not contraindicate the transfusion of PRBCs using a PICC. Another study showed that PRBC transfusion performed in vitro through 24-gauge silicone and 28-gauge polyurethane PICCs was feasible without detectable hemolysis 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, there was a concomitant infusion of pRBC to TPN, which constitutes a risk factor (10) . In an experimental study conducted in a university hospital in Geneva, whose objective was to demonstrate the safety of pRBC transfusions through PICC 1 and 2 Fr, compared with transfusions through the peripheral venous catheter, no statistically significant differences were found between the control and experimental groups and no evidence of obstruction (11) . The authors highlight the need to develop prospective studies that evaluate different variables, so that the catheter caliber may not be identified as the only interfering factor in the obstruction of the catheter, with the need for deepening of the topic.…”
Section: Peripherally Inserted Central Catheter Obstruction In Packed...mentioning
confidence: 97%
“…A retrospective study, whose objective was to assess the occurrence of obstruction after the administration of red blood cells in preterm NB through 1Fr PICC, identified the incidence of catheter obstruction of 2.6% of transfusion cases (10) . Another study, which compared transfusions of packed red blood cells (pRBCs) using PICC 1 and 2 Fr and peripheral venous catheter, found no evidence of obstruction (11) .…”
Section: Introductionmentioning
confidence: 99%